AlMalaqi grammatical opinions in Mughni Al-Labib's Book: A linguistic descriptive study - Burini, Ahyaf Abdel Azeze (Arab Journal for Sciences and Research Publishing, 2020)
This paper is concerned with studying Al-Maliqi’s grammatical opinions, which mentioned in Mughni al-Labib by Ibn Hisham Al-Ansari, as it deals with the study six grammatical opinions mentioned by Ibn Hisham explicitly to al-Mulqi, these opinions came in a sequence according to the way they were presented in the book, and they were discussed by showing the opinion of Al-Maliqi, then Ibn Hisham, and the researcher's opinion. The study concluded that Ibn Hisham was not an imitation of one of the grammatical doctrines. Based on grammatical principles; Especially the origin of hearing, Ibn Hisham took frequent Quranic readings, and considered the noble prophetic hadith, and poetry in the ages of his protest, and he was not imitating a particular school, but rather brought together these schools, and came out with some opinions about it. Based on the results, a number of recommendations and proposals were presented.
Keywords: The answer particle (أجل); One of the meanings of (أما); The emphatic lam